Development of an automated sand sieve machine - Othman, Muhamad Akmal; Kamardin, Nur Kamarliah (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
The project aims to develop an automatic sand sieve machine to enhance efficiency at construction sites by separating sand from stones more effectively than traditional manual methods. The manual method requires human effort, more time consuming and labour cost. By using this automated sand sieve machines, these issues can be effectively addressed. The design process begins with studying the limitations of existing methods and examining user requirements to develop improved design concepts. Detailed engineering drawings are produced using SolidWorks to direct the fabrication process, which includes component assembly, cutting, welding, and material selection. Improved sand filtering effectiveness as well as a decrease in the effort and cost involved in the sand sieving process are the expected outcomes.